Participation motivation in sport: a study on taekwondo athletes - Abdulmenaf Korkutata (Selcuk University, 2016)
The interest in the sport, participation motivation in sport is a significant influencing factor. Motivation has an effect on many cognitive processes that affect success. Therefore, depending On level of motivation of the athletes interest in the sport are wondering whether they present the difference of participation in sport. Interest in the sport and participation motivation in sport previously not found in the native literature a survey of this topic makes it important.This research interest and participation motivation in the sport of Taekwondo athletes according to demographic variables that aims to discover whether there is any difference. For this,94 female,144 Male,238 Taekwondo athletes in total on an empirical research was conducted.The scope of the research, the data needed for this research were obtained through a survey designed and data collected were analyzed using statistical methods.According to research findings, the period of weekly training, can't show any difference in terms of motivation and interest in the sport, however, according to the athletes age groups, genders, their year in sports (experience)and their educational level significant statistical differences were determined.